2018
DOI: 10.1111/tri.13112
|View full text |Cite
|
Sign up to set email alerts
|

Personalized subcutaneous administration of hepatitis B surface antibodies without nucleos(t)ide analogs for patients at risk of renal failure after liver transplantation: a prospective single center cohort study

Abstract: Currently, nucleos(t)ide analogs (NAs) in monotherapy are favored as prophylaxis against hepatitis B recurrence after liver transplantation. However, in patients at risk of renal failure, renal safety of NAs is of concern. We investigated the safety and efficacy of subcutaneous (SC) hepatitis B immunoglobulins (HBIG) in monotherapy. This is a single-arm prospective trial in patients transplanted >1 year. We included 43 Caucasian patients. The majority was treated with calcineurin inhibitors, and several patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…HBIG is definitely effective, however it may mask HBV‐replication if an inadequate NUC‐based replication occurs . An advantage of HBIG as monoprophylaxis may still be seen in patients with renal insufficiency . Adequate prophylaxis might help to control recurrence but should be adjusted to each recipient and especially discontinuation of HBIG can be reevaluated during the long‐term run.…”
Section: Discussionmentioning
confidence: 99%
“…HBIG is definitely effective, however it may mask HBV‐replication if an inadequate NUC‐based replication occurs . An advantage of HBIG as monoprophylaxis may still be seen in patients with renal insufficiency . Adequate prophylaxis might help to control recurrence but should be adjusted to each recipient and especially discontinuation of HBIG can be reevaluated during the long‐term run.…”
Section: Discussionmentioning
confidence: 99%
“…In a German multicentre study, patients’ compliance to SC HBIG at home was high, no discontinuation caused by adverse events was reported and mean anti‐HBs levels at the final visit were above the threshold of 100 IU/L, while no HBV recurrence was observed 34 . Bielen et al 35 confirmed the long‐term efficacy and safety of SC HBIG monoprophylaxis after LT in patients with impaired renal function or at high risk of renal failure, in whom the administration of NAs may increase the risk of nephrotoxicity. Interestingly, it was recently shown that switching from IV or IM HBIG to SC HBIG significantly improves quality of life after LT, by reducing the frequency of side effects and their impact on daily activities, by reducing negative feelings and by increasing patients’ autonomy 36 (Table 1).…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 92%
“…Another multicentre study evidenced that the early introduction of SC HBIG by week 3 after LT, in combination with NA, effectively prevented HBV recurrence, with no treatment failures reported 38 . Currently, many study groups 33‐35 support switching from IV/IM to SC HBIG after at least 6‐12 months post‐LT in patients without HBV recurrence and with adequate anti‐HBs serum levels in order to ensure safe transition from parenteral to SC administration of HBIG. Hwang et al 57 recently suggested an individualized HBV prophylaxis protocol by estimating simulative half‐life (SHL) of HBIG using clinically available parameters, including patient's gender, body weight, haematocrit, infusion intervals of HBIG and trough levels of anti‐HBs.…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%
“…The safety and efficacy of subcutaneous HBIg monotherapy was investigated in a prospective study, showing 100% success rate (no HBV recurrence) after a mean follow-up period of 36±5 months, without worsening of kidney function; this suggested that HBIg monotherapy was not only highly effective in preventing recurrence but also not associated with deleterious renal effects, which is a risk with the use of certain NAs. 28 Target antibody levels for patients at high risk of recurrence (such as those positive for HBV DNA pre-LT) was $200 IU/L, and those at lower risk was $150 IU/L. However, it is important to note that this study included only 43 patients, all Caucasian in origin, all HBsAg-and HBV DNA-negative at inclusion.…”
Section: Hbig Monotherapymentioning
confidence: 95%